2018
DOI: 10.1016/j.molmet.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

The incretin hormone GIP is upregulated in patients with atherosclerosis and stabilizes plaques in ApoE−/− mice by blocking monocyte/macrophage activation

Abstract: ObjectiveThe incretin hormones GLP-1 (glucagon-like peptide-1) and GIP (glucose-dependent insulinotropic peptide) are secreted by the gut after food intake leading to pancreatic insulin secretion and glucose lowering. Beyond its role in glucose control, GLP-1 was found in mice and men to beneficially modulate the process of atherosclerosis, which has been linked to improved cardiovascular outcome of patients with diabetes at high cardiovascular risk treated with GLP-1 receptor agonists. However, little is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 18 publications
4
43
0
1
Order By: Relevance
“…This suggests the involvement of GIPR/adenyl cyclase/PKA axis. The anti-inflammatory effects of GIP on monocytes were further demonstrated by a recent study showing that active GIP suppressed the chemokine ligand 2 (CCL2)-induced migration of mouse monocyte RAW 264 cells and human monocyte THP-1 cells thorough reductions in gene expression levels of chemokine receptor type 2 [77]. In addition, active GIP also inhibited the matrix metalloproteinase-9 protein levels and interleukin (IL)-6 production by suppressing LPS-induced activation of nuclear factor-kappa B p65 and mitogen-activated protein kinases in mouse monocyte RAW 264 cells [77].…”
Section: Monocytes Macrophages and Adipocytesmentioning
confidence: 93%
See 3 more Smart Citations
“…This suggests the involvement of GIPR/adenyl cyclase/PKA axis. The anti-inflammatory effects of GIP on monocytes were further demonstrated by a recent study showing that active GIP suppressed the chemokine ligand 2 (CCL2)-induced migration of mouse monocyte RAW 264 cells and human monocyte THP-1 cells thorough reductions in gene expression levels of chemokine receptor type 2 [77]. In addition, active GIP also inhibited the matrix metalloproteinase-9 protein levels and interleukin (IL)-6 production by suppressing LPS-induced activation of nuclear factor-kappa B p65 and mitogen-activated protein kinases in mouse monocyte RAW 264 cells [77].…”
Section: Monocytes Macrophages and Adipocytesmentioning
confidence: 93%
“…Indeed, a couple of studies showed the anti-inflammatory effects of GIP in immune cells (Table 1) [76,77]. GIP ranging from 1 to 100 nM dose-dependently suppressed the lipopolysaccharide (LPS)-induced gene expression levels of tumor necrosis factor (TNF) or inducible NOS in human monocyte THP-1 cells, and these effects were abolished by inhibiting adenyl cyclase or PKA, but not exchange protein directly activated by cAMP 2 [76].…”
Section: Monocytes Macrophages and Adipocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…25 In addition to these effects in β cells and adipose tissue, GIP/GIPR has been reported to have various effects on metabolic and cardiovascular diseases. GIP/GIPR agonism is vasoprotective in atherosclerosis patients, 26 whereas, in contrast, disruption of GIP/GIPR is beneficial after myocardial infarction. 27 These findings broaden the system that needs to be considered when developing new drugs that modulate the GIP/GIPR axis.…”
Section: Study Populations and The Effect Of Gipr Variants On Phenomentioning
confidence: 99%